Situation of Refugees in Warzone of The World and their Legal Issues - Iqbal, Muhammad Ahsan; Mukhtar, Hamid; Saleem, Hafiz Abdul Rehman (Pakistan Journal of Humanities and Social Sciences, 2024)
This paper examines the legal challenges faced by refugees in disaster areas and the challenges they face in accessing essential rights and protections. The paper begins by presenting the scale of the global displacement emergency and the unique challenges refugees face in the context of disaster areas. It then examines the legal framework governing refugee status under international regulation, including the 1951 Refugee Convention, and discusses the challenges associated with its implementation and overseeing it. The article additionally addresses the challenges that refugees face in disaster areas, including limited access to education, health care, and employment. Operations, including dangers of exploitation, dealing, and abuse. The paper concludes with recommendations to address these issues, including increasing subsidizing, legal protection, increasing access to education and employment, and strengthening the option to live. Abroad, improve cooperation, and address the main drivers of conflict and violence. Overall, this article features the urgent need for action to protect the rights of refugees in conflict zones and ensure their safety, well-being and integration into new societies. The protection and rights of refugees isn't only an ethical imperative yet in addition a legal obligation under international regulation and it is the responsibility, everything being equal, to ensure that these obligations are met.